Mechanical stress and thermal aspects of the rotor assembly for turbomolecular pumps. (July 2016) - Huang, Ziyuan; Han, Bangcheng; Mao, Kun; Peng, Cong; Fang, Jiancheng
Abstract: Due to the high speed and the high power density, the blade strength and the rotor overheating of a turbomolecular pump (TMP) are strongly related to the safety and the stability of the pump operation. For magnetically levitated TMPs, which can obtain an ultra-clean and ultra-high vacuum in comparison to traditional TMPs with oil-lubricated bearings, the rotor strength and overheating are limiting their ultimate pumping speed, since the rotor is only cooled by thermal radiation. This paper focuses on the stress analysis of the pump and the rotor thermal performance evaluation to prevent the permanent magnets (PMs) from irreversible demagnetization at high temperature and to ensure the rotor integrity throughout the whole speed range. The influence of the thickness of the sleeve around the PMs of the rotor shaft on electromagnetic losses and stress is analyzed. Finally, the electromagnetic and thermal tests are implemented on a prototype to verify the theoretical methods and the design concept. The measured maximum pumping speed of the prototype can reach 4180 L /s. Highlights: A novel magnetically levitated Turbo Molecular Pump is designed for the ultra-clean environment. A high speed permanent-magnet machine is chosen and designed to driven the Turbo Molecular Pump. The stress analysis of the machine and the rotor thermal performance evaluation is executed in this paper. The prototype is manufactured and tested to verify the theoretical method and the design concept.